Social issues in sport communication you make the call - Rentner, Terry L.; Burns, David P.
"Combining theory with practical application, this collection of real-life, provocative case studies on social issues in sports provides students with the opportunity to make the call on ethical and professional dilemmas faced by a variety of sport and communication professionals. The case studies examine the successes and failures of communication in the corporate culture of sport intersecting with social issues including race, gender, religion, social media, mass media, public health, and LGBTQ+ issues. Topics include the COVID-19 pandemic, the Black Lives Matter movement, sexual abuse scandals, domestic violence, cultural appropriation, and mental health. Each chapter contextualizes a specific issue, presents relevant theory and practical communication principles, and leads into discussion questions to prompt critical reflection. The book encourages students to view the evidence themselves, consider competing ethical and professional claims, and formulate practical responses. This collection serves as a scholarly text for courses in sport communication, business, intercultural communication, public relations, journalism, media studies, and sport management"--Provided by publisher.